Stocktaking methods of facilities in a state of ruin - Drobek, Katarzyna; Szostak, Bartosz; Królikowski, Wojciech (Protection of Cultural Heritage, 2018)
The measured building survey is the basic form of presenting and protecting the object of the historic ruin. It also allows us to control the behavior and the progress of the degradation of the object. The ruined objects are very specific because they usually contain not all elements of an traditional building object. This means that the methods and methods of inventory taking, as in the case of traditional objects, may not be sufficient. Elements of objects in ruins often have complicated and diverse geometry, difficult and not completely safe access to all elements. The publication presents methods that can be helpful in the inventory of such objects. Each method describes the necessary instruments, the method of taking measurements, accuracy, advantages and limitations. The paper also presents examples of application for selected methods.